Pure maxillofacial trauma and its correlation with neurobehavioural alteration amongst Malaysian: A longitudinal study / Nor ‘Izzati Mohtar - Nor ‘Izzati , Mohtar (2017)
Purpose of the Study: This research was performed to report the neurobehavioural alterations and brain microstructural changes in patients following pure maxillofacial trauma attending the Department of Emergency Medicine, University Malaya Medical Centre. The affiliation between the specific maxillofacial injury and its effect on the brain microstructural injury; and how the both former impacted the neurobehavioural deficits were investigated. Material and Methods: A total of 16 subjects with maxillofacial trauma were included in this one-year logitudinal study. A pro-forma was developed to assist data collection. The data included demographic details, aetiology, clinical findings and radiograph investigations. All the subjects then underwent magnetic resonance imaging diffusion tensor imaging (MRI DTI), neurobehavioural assessment using Neurobehavioural Symptom Inventory (NSI) and The Hamilton Rating Scale for Depression (HAM-D) questionnaire. During the follow-up review, 6 subjects were able to complete the neurobehavioural assessment and only 4 completed both MRI DTI and neurobehavioural assessments. There were also 16 healthy subjects for control. Descriptive test was used to establish demographic data. Due to the initial and follow-up subject numbers discrepancy, non-parametric tests of Mann-Whitney U, Kruskal Wallis, Wilcoxon Signed Rank and Spearman’s correlation tests were used in analysing intergroup and intra-group differences and correlation. Results: The involved subjects were mainly male (n =12), adult (mean age 28.8 ± 6.45) with 11.94 ± 1.39 years of education. The maxillofacial injuries involved were soft tissue injury (n=4), and combination of soft and hard tissue injuries (n=12) with 82.9% fracture involving middle third area. There were non-significant difference in both NSI and HAM-D score in the initial and follow-up review. There were also no significant relationship amongst initial and follow-up assessment in test group for the MRI DTI variables – fractional anisotropy (FA),axial diffusivity (AD), median diffusivity (MD) and radial diffusivity (RD).However, there were significant differences between control and test group. Conclusions: The maxillofacial trauma injury had the possibility to cause microstructural brain changes and alter the behaviour presentation after the trauma event, though not significant.